Bronchiectasis: Etiology, Diagnostic Modalities, and Surgical Management - Hussen, Waleed M.; Jaber , Sabah N.; Mohammed, Nabeel H. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Bronchiectasis is a chronic disease characterized mainly by chronic cough with the production of purulent sputum. It is still seen in Iraq and developing countries, although its incidence is much lower in the developed countries. Objectives: To highlight the etiology and the diagnostic workup of patients affected by this disease process and to assess the outcome of the surgical intervention in a properly selected patient. Methods: Fifty-six patients were enrolled in the current study. Thirty patients were excluded as they were not surgical candidates. Twenty-six patients met our criteria, as they were surgical candidates, whose files were studied retrospectively. All the cases were admitted to the Thoracic and Vascular Department of the Surgical Specialties Hospital of the Medical City Teaching Complex, Baghdad/ Iraq, from 1st January 2018 to 31st December 2022. All cases underwent pre-operative blood investigations, diagnostic imaging, and bronchoscopy. They were subjected to surgeries with different resection procedures. Results: Twenty of the cases were females (76.9%). while six patients were male (23.1%). The youngest patient was a seven-year-old female and the oldest was a 59-year-old male. The mean age was 27.3 years, and the median was 33 years. The most common symptoms were cough with purulent sputum. A CT scan of the chest was performed on all patients. The right middle lobe and the left lower lobe were the most affected. Twenty-five patients underwent classical postero-lateral thoracotomy. The right middle lobe and the left lower lobe were the most common lobes resected. Only one patient underwent video-assisted thoracoscopic surgery (VATS). The histopathological results were consistent with bronchiectasis in 24 patients. Post-operative morbidity included atelectasis and wound infection in one patient, they were managed successfully medically. No mortality was reported in the study. Conclusion: Once bronchiectasis is well-established, surgery in properly selected patients, with complete resection of the involved lobe or lobes, offers the best chance of cure and optimum control of the patient’s symptoms.